ROLE OF REZEKNE RETIREMENT DAY CENTRE IN IMPROVING THE QUALITY OF LIFE OF SENIORS - Matule, Erika; Danilane, Liga (Education Reform: Education Content Research and Implementation Problems, 2022)
Life expectancy is increasing worldwide, and the proportion of seniors, which poses challenges to ensure that all individuals, regardless of their age, enjoy equal opportunities in both the private sector and the labour market, regardless of their state of health, without adversely affecting quality of life components.The purpose of the scientific article is to find out how the quality of life of Seniors is affected and how it is influenced by the functioning of the Senior Day Center, to improve the quality of services and collateral of the Senior Day Centre in Rezekne.